Insular Celtic as a Language Area - Matasović, Ranko (Array, 2007)
In order to properly subclassify languages belonging to a single branch of a language family, we must know not only which isoglosses they share, but also whether those isoglosses represent shared innovations, rather than archaisms, and also whether they are exclusive, i.e. not shared by other, perhaps extinct, languages of that branch. Moreover, the exclusive shared innovations must not be the result of language contact occurring after the initial separation of the subclassified languages.